2023
DOI: 10.1029/2022jc019272
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Equatorially Forced Waves in Triggering Benguela Niño/Niña as Investigated by an Energy Flux Diagnosis

Abstract: Equatorial Kelvin waves in the tropical Atlantic Ocean excite coastally trapped Kelvin waves (CTWs) at the eastern boundary, by which they transport their energy poleward to the very productive nearshore region in the South Atlantic, the Angolan and Benguela upwelling region (from 5°S to around 30°S, hereafter referred to as ABU region) (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…In fact, the role of remote forcing via the propagation of a Kelvin wave was not the most pronounced in the 1995 Benguela Niño in comparison with other warm event years (e.g., 1984see Figure 6 from Imbol Koungue et al, 2019). More recently, Song et al (2023) when simulating Benguela Niño/Niña events with a single-layer ocean linear model excluding the local forcings (e.g., precipitation and freshwater advection) did not find a clear energy route 10.1029/2023JC020241 3 of 18 of equatorial waves (i.e., remote forcing) triggering the 1995 extreme warm event. The authors suggested that the coastal SST anomaly might have been forced locally for this year (Song et al, 2023).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the role of remote forcing via the propagation of a Kelvin wave was not the most pronounced in the 1995 Benguela Niño in comparison with other warm event years (e.g., 1984see Figure 6 from Imbol Koungue et al, 2019). More recently, Song et al (2023) when simulating Benguela Niño/Niña events with a single-layer ocean linear model excluding the local forcings (e.g., precipitation and freshwater advection) did not find a clear energy route 10.1029/2023JC020241 3 of 18 of equatorial waves (i.e., remote forcing) triggering the 1995 extreme warm event. The authors suggested that the coastal SST anomaly might have been forced locally for this year (Song et al, 2023).…”
mentioning
confidence: 99%
“…More recently, Song et al (2023) when simulating Benguela Niño/Niña events with a single-layer ocean linear model excluding the local forcings (e.g., precipitation and freshwater advection) did not find a clear energy route 10.1029/2023JC020241 3 of 18 of equatorial waves (i.e., remote forcing) triggering the 1995 extreme warm event. The authors suggested that the coastal SST anomaly might have been forced locally for this year (Song et al, 2023). Finally, in Gammelsrød et al (1998), Conductivity-Temperature-Depth (CTD) profiles identified the presence of a freshwater plume of low salinity at 18°S in March 1995, much further south than climatologically expected (i.e., maximum southward displacement extending only to around 12°S in February-March-April; Awo et al, 2022).…”
mentioning
confidence: 99%